1999
DOI: 10.1007/s004050050165
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular hemangioma of the masseter muscle

Abstract: Intramuscular hemangiomas (IMH) are uncommon tumors of the head and neck, but often occur in the trunk and extremities. When present in the head, the masseter muscle is the most frequently involved site, although constituting only 0.8% of all hemangiomas. Accurate preoperative diagnosis is uncommon without cytology or biopsy. A case of IMH of the masseter muscle in a 24-year-old Turkish woman is presented. Clinical, radiologic and histologic findings and treatment modalities are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
1
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 7 publications
0
60
1
3
Order By: Relevance
“…MR imaging has been shown to provide better detection and delineation of the extent of intramuscular hemangioma than CT. Furthermore, MR imaging is superior because of the distinct contrast between normal muscle and the intramuscular hemangioma that results from the presence of nonvascular tissue, fat, smooth muscle, fibrous and myxoid tissue, thrombus, hemosiderin, and bone [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…MR imaging has been shown to provide better detection and delineation of the extent of intramuscular hemangioma than CT. Furthermore, MR imaging is superior because of the distinct contrast between normal muscle and the intramuscular hemangioma that results from the presence of nonvascular tissue, fat, smooth muscle, fibrous and myxoid tissue, thrombus, hemosiderin, and bone [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The masseter (36%), followed by the trapezius (24%), are the muscles most frequently affected. 6 However, hemangioma in the temporalis muscle is rarely reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The masseter (36%), followed by the trapezius (24%), are the muscles most frequently affected. 6 However, hemangioma in the temporalis muscle is rarely reported in the literature. To the best of our knowledge, in the international literature, Bucci et al 8 reported a review of temporal muscle hemangiomas, which has shown that 24 cases exist in the literature as of 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Although IMHs show an equal sex distribution, involvement of the masseter muscle has a definite male predominance 13. The common complaint is the presence of a painful, slow growing mass with no aesthetic concerns 14. The lesion does not usually show any of the vascular signs such as thrill or skin discolouration that are characteristic of superficial haemangiomas 12…”
Section: Discussionmentioning
confidence: 99%